Teaching descriptive statistics using R - Dedi Rosadi; Khabib Mustofa; Iman Sanjaya; Hendra Perdana; Krisna Mutiara Wati (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2013)
In this paper, we introduce the application of R for teaching statistics descriptive subject which is usually given in the undergraduate statistics course. As an illustration, we will consider the use of R for teaching the subject frequency distribution table, both using the R-CLI and R-GUI version. The R-GUIversion used here is a part of Rplugin.SPSS which is currently under our extensive development. Rplugin.SPSS is a R Commander Plugin, which is a reorganized and an extented version of the menu of Statistics in R-Commander, a SPSS-like version menu. It can be also considered as the extended version of Rplugin.Econometrics (Rosadi, 2010). Further details and further examples can be found in Rosadi (2011,2013).